Improvement of energy efficiency in the operation of a thermal reactor with submerged combustion apparatus through the cyclic input of energy - Belozerov, Valery; Mahatilova, Anna; Sobol’, Oleg; Subbotinа Valeria; Subbotin, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
We examined the patterns in the formation of MAO-coatings on magnesium alloys. Low density and high specific strength of magnesium alloys is the basis for their widespread use. However, poor corrosion resistance of magnesium alloys limits the scope of their application. This problem is solved by transforming the surface layer of magnesium alloys into the multiphase coatings that consist of crystalline oxides and salts of magnesium. The most effective formulations of electrolytes were selected to ensure obtaining the MAO layers of good quality. We explored the phase composition of coatings, hardness, adhesion between coatings and the base, and their protective properties. It was found that the most effective are the multi-component electrolytes containing alkali NaOH, sodium aluminate NaAlO2 and sodium hexametaphosphate Na5P3O10. The MAO treatment provides strengthening of surface (hardness of coatings is 2000−6600 MPa) and improves protective properties. It is demonstrated that the highest protective properties are displayed by the MAO-coatings that contain in their composition, along with MgO, the MgAl2O4 spinel. Protective properties are improved with an increase in the spinel content. This is due to the fact that the occurrence of spinel in the composition of a coating, in contrast to MgO, is accompanied by the increase in specific volume of the coating, resulting in the occurrence of compressive stresses and, as a consequence, in the formation of thicker coatings. The recommendations are given regarding the changes in the composition of electrolyte and parameters of electrolysis to ensure an increase in spinel in the composition of the coating.